Para uma estética na pornografia - Kämpf, Raquel (2008)
The present study analyses aesthetic elements of pornographic films and its evolution since the beginning of the decade of 1910, passing for films in movies of year 1970 and arriving at the films carried through in VHS in new audiovisuals technologies. The observed aesthetic transformations are related to the cultural transformations of occidental society throughout this period. From the concept of pornography and its relation to the theory of power by Foucault, the study of aesthetic in Freud‟s and Lacan‟s psychoanalysis, from the definition of fetish and culture commodity, and the considerations of Jameson on the end of the narratives and the death of the “I”, one brief analysis of the first films of 1915 became, the films of the decade of 1970, as Deep Throat, Emmanuelle, The History of “O”, and the current pornographic films carried through in digital technology. Key words: aesthetic; pornography; movie; pornographic film.